(untitled) (Inflexion Point Magazine, 2025)
With the presentation of this book of proceedings, we successfully concluded the 5th International Congress of Basic Sciences and Engineering (CICI-2024). This special edition is supported by the journal Punto de Inflexión (ISSN 3028-6425) of the Faculty of Basic Sciences and Engineering (FCBI) of the Universidad de los Llanos. The submission of more than 150 papers and the presentations of renowned international guests in the areas of ENGINEERING: Electronics, Systems, Environment, Processes, and related fields; BASIC SCIENCES: Biology, Mathematics, Chemistry, Physics and Statistics; and ENVIRONMENTAL MANAGEMENT AND ENERGY, demonstrate the strength and maturity with which the congress has developed over the years. The invited speakers showcased the advances in their respective fields of knowledge through workshops and keynote lectures. In the area of ​​physics, Dr. Jorge Luiz Pimentel, through the lecture "Introduction to Raman Spectroscopy and its Applications," demonstrated its application and practical application in topics such as superconductivity, magnetism, and nanomaterials. Dr. Rafael González, with the lecture "Quantum Dance: Rogue Electrons and the Materials of the Future," explored the relationship and advances between the theory of condensed matter physics and its computational tools.